2017
DOI: 10.1136/esmoopen-2017-000165
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint inhibitors in the treatment of urological malignancies

Abstract: Checkpoint inhibitors are monoclonal antibodies attach to several different receptors on T-cells or tumour cells expressing receptors for cytotoxic T-lymphocyte antigen 4 (CTLA-4), programmed death-1 (PD-1) and their ligand (PD-L1). Since 2010, numerous trials on different tumour types have been conducted, which was resulted in these drugs being approved for the treatment of melanoma, lung cancer, Hodgkin's lymphoma and head and neck cancers. Urological cancers, especially urothelial and renal-cell carcinomas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…The success of BCG in treating NMIBC has emphasized BC as an immune sensitive disease, and the role of immune checkpoints inhibitors like pembrolizumab is also being researched in NMIBC patients, relapsing after the BCG treatment (KEYNOTE-057) 51. Inman et al reported that PD-L1 tumor cell expression was associated with increased resistance to BCG therapy, which suggests that TCs might be protected from attack by ICs through immune checkpoints, since a fully functional immune system is prerequisite for BCG efficacy 52.…”
Section: Discussionmentioning
confidence: 99%
“…The success of BCG in treating NMIBC has emphasized BC as an immune sensitive disease, and the role of immune checkpoints inhibitors like pembrolizumab is also being researched in NMIBC patients, relapsing after the BCG treatment (KEYNOTE-057) 51. Inman et al reported that PD-L1 tumor cell expression was associated with increased resistance to BCG therapy, which suggests that TCs might be protected from attack by ICs through immune checkpoints, since a fully functional immune system is prerequisite for BCG efficacy 52.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic synergy of the combination of EBRT (external beam radiation therapy) and iplimumab (monoclonal anti-CTLA-4 antibody) has also been confirmed [4,7,31,41]. A phase III trial in patients with mCRPC who had progressed after docetaxel chemotherapy, compared iplimumab in combination with palliative radiotherapy for bone metastases to radiotherapy alone.…”
Section: Impact Of Monoclonal Antibodies Directed Against Immune Checmentioning
confidence: 98%
“…Recently, immune checkpoint blockade monoclonal antibodies (moAbs) have been demonstrated to be effective for RCC and BC. However, the efficacy is in the range of 20–40% . New therapeutic modalities are needed for patients with refractory disease.…”
mentioning
confidence: 99%